Reading the Book of Revelation politically - De Villiers, Pieter GR (Stellenbosch Theological Journal, 2017)
In this essay the political use of Revelation in the first five centuries will be analysed in greatest detail, with some references to other examples. Focus will be on two trajectories of interpretation: literalist, eschatological readings and symbolic, spiritualizing interpretations of the text. Whilst the first approach reads the book as predictions of future events, the second approach links the text with spiritual themes and contents that do not refer to outstanding events in time and history. The essay will argue that both of these trajectories are ultimately determined by political considerations. In a final section, a contemporary reading of Revelation will be analysed in order to illustrate the continuing and important presence of political readings in the reception history of Revelation, albeit in new, unique forms.